Identification and Crystallization of Penicillin-Binding Protein/β-Lactamase Homolog (Rp46) from Ruegeria Pomeroyi - Bum Han Ryu; Tri Duc Ngo; Wanki Yoo; Kyeong Kyu Kim; T. Doohun Kim (Crystals, 2016)
In spite of the enormous biological and clinical significance of penicillin-binding protein (PBP)/β-lactamase (βL), few of their many homologs (PBP)/βLs homologs) have been studied crystallographically, and have known functions. Herein, X-ray crystallographic study of a PBP/βL homolog (Rp46) from Ruegeria pomeroyi is described. Multiple sequence alignments indicate that Rp46 has a conserved serine residue within the S70-X-X-K73 motif (Motif I), acting as the catalytic nucleophile. Moreover, an invariant tyrosine residue (Tyr185) and a Trp365-X-Gly motif (Motif III) were also identified. The recombinant Rp46 protein was expressed in Escherichia coli and purified to homogeneity judging from the SDS-PAGE analysis. Rp46 was crystallized using a solution consisting of 20% (w/v) PEG 3000, 0.1 M Tris-HCl, pH 7.0, 0.2 M calcium acetate, and the X-ray diffraction data were collected to a resolution of 1.90 Å with an Rmerge of 7.4%. The crystals of Rp46 belong to the space group I422, with unit cell parameters a = b = 141.26 Å, and c = 119.75. The structure determination and biochemical characterization are in progress. (Synopsis: A penicillin-binding protein/β-lactamase homolog (Rp46) from Ruegeria pomeroyi was identified and crystallized in the space group I4, and the diffraction data were collected to a resolution of 1.90 Å.)